Population ageing: Alternative measures of dependency and implications for the future of work - Claire Harasty; Martin Ostermeier (International Labour Organization (ILO), 2020)
The world's population is getting older, a phenomenon that has important implications for the future of work. Persons aged 55 years and over are expected to outnumber all children aged 0 to 14 years by 2035 and the entire child and youth population aged 0 to 24 years by 2080. As a direct consequence of population ageing, the number of older workers aged 55 to 64 years is increasing and is set to equal one quarter of the global labour force by 2030. This paper examines the projected labour force participation trends of older workers to 2030 and discusses the future of economic dependency for developing, emerging and developed countries. It introduces five alternative measures of economic dependency to account for the fact that persons of working age may not be working or may be facing employment conditions that compromise their capacity to support themselves and others. Such conditions include scenarios where workers are unable to work as many hours as they would like, or where they are in situations of vulnerable employment or working poverty. These alternative measures therefore not only take into account demographic and quantitative labour market characteristics, such as age structure, activity status and unemployment, but also consider qualitative dimensions such as underemployment, labour income and vulnerability. Using a very rich ILO data set that provides a consistent series of labour market data for all countries with forecasts to 2024 and beyond, the paper provides estimates for these new dependency measures and makes a number of policy recommendations to address the impact of ageing on decent work.
Keywords: 330; future of work; ageing population